2017
DOI: 10.3390/nu9070658
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Identification of Geriatric Patients with Hypovitaminosis D: The ‘Vitamin D Status Predictor for Geriatrics’ Study

Abstract: The 16-item Vitamin D Status Predictor (VDSP) tool identifies healthy older community-dwellers at risk of hypovitaminosis D and may guide the use of blood tests in this population. The objective of the present hospital-based study was to test the efficacy of the VDSP to identify geriatric patients with hypovitaminosis D. The study included 199 nonsupplemented geriatric in- and outpatients consecutively admitted to Angers University Hospital, France (mean ± SD, 82.0 ± 7.8 years; 53.3% female). Serum 25-hydroxyv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…This result seems to be inconsistent with the findings of some previous studies. [ 56 ],[ 57 ],[ 58 ],[ 59 ],[ 60 ] These studies have reported that the low 25(OH)D levels in the elderly were seen more commonly in women compared to men.…”
Section: Discussionmentioning
confidence: 99%
“…This result seems to be inconsistent with the findings of some previous studies. [ 56 ],[ 57 ],[ 58 ],[ 59 ],[ 60 ] These studies have reported that the low 25(OH)D levels in the elderly were seen more commonly in women compared to men.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of hypovitaminosis D in the elderly is known to be even higher than the general population. 2,34 Fortunately, when patients are actively treated for vitamin D deficiency (even those with metabolic bone disease), the rate of vitamin D deficiency is much lower (4.6%), 4 demonstrating that concerted intervention can be effective. 6 Even better, preventive measures could help decrease the burden of fragility fractures for patients and society alike.…”
Section: Discussionmentioning
confidence: 99%
“…We studied in- and outpatients aged 65 and over consecutively recruited in the VDSP-G (Vitamin D Status Predictor for Geriatrics) study. The VDSP-G study is an observational cross-sectional study designed to apply the VDSP among all patients consecutively hospitalized or seen in consultation in the geriatric acute care unit of the University Hospital of Angers, France, from March to May 2015 [ 14 ]. After giving their written informed consent for research, included participants received a full medical examination consisting of a self-administered VDSP questionnaire, various rater-administered structured questionnaires and a standardized clinical examination.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the algorithms previously published [ 13 ] were applied to the items of the self-VDSP to identify among participants those with probable severe vitamin D deficiency (i.e., serum 25(OH)D ≤25nmol/L), vitamin D deficiency (i.e., serum 25(OH)D ≤50nmol/L) or vitamin D insufficiency (i.e., serum 25(OH)D ≤75nmol/L) [ 1 ]. Briefly, the VDSP is based on a 16-item questionnaire coupled with combinatorial non-linear algorithms that were built from models of feed forward artificial neural networks (multilayer perceptron) [ 13 , 14 ]. In practice, clinicians submit the 16 responses to the tool, which combines them using three dedicated algorithms to identify severe vitamin D deficiency, deficiency or insufficiency.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation